2016
DOI: 10.1002/bies.201670911
|View full text |Cite
|
Sign up to set email alerts
|

The hypoxic microenvironment: A determinant of cancer stem cell evolution

Abstract: Tumors are often viewed as unique entities with specific behaviors. However, tumors are a mixture of differentially evolved subpopulations of cells in constant Darwinian evolution, selecting the fittest clone and allowing it to outgrow the rest. As in the natural environment, the niche defines the properties the fittest clones must possess. Therefore, there can be multiple fit clones because of the various microenvironments inside a single tumor. Hypoxia is considered to be a major feature of the tumor microen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 168 publications
1
111
0
Order By: Relevance
“…COX-2 in the tumor microenvironment was critical for the induction and maintenance of cancer stemness 53. It is known a hypoxic microenvironment and hypoxia-inducible factor-1α (HIF-1α) perform a critical role in maintaining the stemness of CSCs 54, 55. Csiki et al reported that HIF-1α activated the transcription of COX-2 by interaction with the PTGS2 promoter in non-small cell lung cancer cell 56.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 in the tumor microenvironment was critical for the induction and maintenance of cancer stemness 53. It is known a hypoxic microenvironment and hypoxia-inducible factor-1α (HIF-1α) perform a critical role in maintaining the stemness of CSCs 54, 55. Csiki et al reported that HIF-1α activated the transcription of COX-2 by interaction with the PTGS2 promoter in non-small cell lung cancer cell 56.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α induced by hypoxia has been found to promote upregulation of Snail and to attenuate the expression of E-cadherin, leading to EMT and increased cancer aggressiveness [21]. Hypoxia and induction of HIF-1α have also been shown to expand the subpopulation of cancer stem-like cells and to increase resistance to therapies in various cancer types [22,23,24]. Although a direct involvement of increased expression of HIF-1α under hypoxia is understandable, we have observed a relatively high basal level of HIF-1α in one of the analyzed HNSCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that through self-renewal and differentiation, cancer stem cells are responsible for the production of the various tumor cell types and contribute to tumor heterogeneity. Furthermore, according to this hypothesis, tumor metastases and resistance to therapies arise directly from cancer stem cells [25]. Cancer-initiating stem cells have been isolated in leukaemia and in solid tumors such as breast, lung and gynecologycal malignancies [26].…”
Section: Introductionmentioning
confidence: 99%